Complications in Robotic Urologic Surgery (Springer International Publishing, 2018)
This text examines precisely all possible scenarios about robotic urologic surgery where a complication may arise, in order that the surgeon knows all the risk factors that predispose a complication, and if it is presented, to have all anatomical, surgical and updated scientific elements to resolve the situation successfully. The book's content is designed for easy and thorough reading. It is organized in sections that include an overview of robotic surgery, principles of anesthesia and complications, as well as recognition of failure in the instruments used in this kind of surgery. It then offers a detailed discussion of each robotic urologic surgical procedures, both the upper urinary tract, lower urinary tract, oncological procedures, reconstructive and those that are managed in conjunction with other specialties such as gynecology, pediatrics, and other highly specialized as the case of kidney transplantation. Chapters are written by experts in the field who indicate step by step review of each clinical case in particular to prevent the occurrence of associated complications, including providing information on legal aspects. The book is written for both novice surgeons and all those experts who interact daily in the wonderful world of robotic surgery. Containing the points of view and recommendations of the most experienced surgeons in each of the procedures, it is as if the professor were in the operating room with the surgeon to explain how to prevent, identify and treat complications. Complications in Robotic Urologic Surgery represents the complete collection of all the stages of complications in urologic robotic surgery and will be indispensable for all robotic surgeons.